Implementasi Pull Strategy Marketing Public Relation dalam Meningkatkan Kunjungan Wisatawan ke Desa Wisata Keling Kabupaten Kediri - Alex Agung Tri Laksono; Sheidy Yudhiasta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The contribution of the tourism sector to the Indonesian economy is very large. In 2022 the tourism sector will contribute to the country's GDP (Gross Domestic Product) by 4.3 percent or IDR 842,303.16 billion (BPS, 2022). Tourists have an important role in the tourism industry. Tourist visits make tourism destinations come alive by spending money and participating in the activities offered (Hanif, et al. 2016). A tourist destination has different marketing implementations to attract tourist interest (Junaedi, et al. 2021) The tourism promotion strategy that has been carried out by Keling Rural Tourism uses a marketing public relations strategy to attract tourists. One of the functions of public relations is the deliberate dissemination of information with planning and management in it (Satria and Hidriani, 2021). This research uses a qualitative descriptive method. In this research, the data collection method uses interviews, observation and documentation. Interviews were conducted by determining key informants. Because key informants are considered to be the informants who know and understand all the information needed to conduct research (Sugiyono, 2018). ). The data analysis technique is carried out by reviewing all data obtained through interviews and observations. Then the author carries out reduction by writing a summary and sorting the data according to its categories. The data that has been sorted is then presented with descriptive analysis and finally conclusions are drawn. The results of the research show that the implementation of Pull Marketing Public Relations in Keling Rural Tourism in increasing tourist visits has made various efforts including social media activation, digital media publications, promotions, events and the use of banners. Of the five efforts to use banners, the implementation is the most inappropriate, while events are the implementation that is most capable of attracting tourist visits. Further research needs to be carried out, such as focusing on the management of the Keling Rural Tourism